The process of reverse logistics as a practice of preserving the environment:t he case of agricultural producers in the District of Santa Flora/RS - Boemo, Roberto Vasconcelos; Denardin, Élio Sérgio; Medeiros, Natane de Cassia Leivas de; Medeiros, Flaviani Souto Bolzan; Piveta, Maíra Nunes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The continuous search for sustainability and the gradual reduction of impacts to the environment is the goal of most companies that aims to increase its competitiveness in the market. Contributing to this effect, the reverse logistics became part of the strategic planning for many organizations seeking to contribute to the economic and social development of the place where they are inserted, in addition to suit the standards of environmentally appropriate disposal of solid waste. Before this, this article aims to check the support offeredby the manufacturers of agrochemicals, resellers and/or Government to encourage the proper disposal or return of empty containers of chemicals in the perception of agricultural producers of the District of Santa Flora/RS. For this a questionnaire was applied to a sample composed of twenty producers of that district. The results showed that the main reasons forthe return or for submission to the appropriate disposal of empty containers are the legal aspectand the preservation of the environment. When questionedabout the main difficulties faced to make the appropriate disposition, the most pointed transportation as the most relevant factor.